Finding the Reasons of Using the Flouted Maxims in the Utterances of Adaline in the Age of Adaline Movie Subtitle - Novita Ayu Laraswati (ELLITE, 2018)
People sometimes flout the maxims of Cooperative Principle in speaking becausethey imply something in their utterance. To get the implied meaning of thespeaker, the theory of cooperative principles and context are used to analyzethe utterance. This article is aimed to analyze the types of maxim being floutedand the factors that influence the use of flouted maxim in a movie. The sourceof the data used in this research are taken from a movie subtitle entitled TheAge of Adaline (2015) directed by Lee Toland Krieger. This is a qualitative and quantitative research. The qualitative method is applied to analyze the data whereas the quantitative is used to count the number of each flouted maxim.The results of this research show that there are four types of flouted maxim usedby the main character in The Age of Adaline movie, they are: flouted maxim ofrelation, flouted maxim of quantity, flouted maxim of manner, flouted maximof quality. The writer also found the factors influenced the characters to floutthe maxim. The main character flouts the Maxim of Manner because she wantsto end the conversation. Another flouted maxim is Maxim of Quantity. Thereason is Adaline wants to give more information to the hearer about something.The reason of Adaline flouts the maxim of Relation is because she wants tohide something. The reasons why the character flouts the Maxim of Quality isto tease the hearer. Additionally, Adaline as the main character in The Age ofAdaline movie also flout two maxims in an utterance. The reason is that shewants to emphasize her intentions.